Better prognosis of gastric cancer patients with high levels of tumor infiltrating lymphocytes is counteracted by PD-1 expression. (1st January 2020) - Pötzsch, M.; Berg, E.; Hummel, M.; Stein, U.; von Winterfeld, M.; Jöhrens, K.; Rau, B.; Daum, S.; Treese, C.
ABSTRACT: The prognostic potential of anti-tumor immune responses is becoming increasingly important in adenocarcinoma of the gastroesophageal junction and stomach (AGE/S) especially regarding the use of immune checkpoint inhibitors. This study analyzes for the first time the prognostic impact of tumor-infiltrating lymphocytes (TILs) and checkpoint inhibitors in a large Caucasian cohort in patients with AGE/S. We screened tissue samples from 438 therapy-naïve patients with AGE/S undergoing surgery between 1992 and 2005, examined in a tissue microarray (TMA) and stained against human CD3, CD4, CD8, PD-1, and PD-L1. Out of 438 tissue samples, 210 were eligible for multivariate analysis. This revealed that high infiltration with CD3 +, CD4 +, or CD8 + TILs was associated with an increased overall survival in AGE/S patients, which could only be confirmed in multivariate analysis for CD3 (HR: 0.326; p = .023). Independent improved survival was limited to gastric cancer patients and to early tumor stages as long as TILs did not express PD-1 (HR: 1.522; p = .021). Subgroup analyses indicate that TIL-dependent anti-tumor immune response is only effective in gastric cancer patients in early stages of disease in PD-1 negative TILs. Combined analysis of PD-1 and CD3 could serve as a prognostic marker for the clinical outcome of gastric cancer patients and could also be of interest for immunotherapy.